An unusual method to diagnose a rare disease: Upper gastrointestinal endoscopy - Düzenli, Tolga; Kaplan, Mustafa; Tanoğlu, Alpaslan; Salmanoğlu, Musa (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Düzenli T, Kaplan M, Tanoğlu A, Salmanoğlu M. An unusual method to diagnose a rare disease: upper gastrointestinal endoscopy. Turk J Gastroenterol 2017; 28: 522-3.